2006
DOI: 10.1176/foc.4.3.360
|View full text |Cite
|
Sign up to set email alerts
|

Neural Mechanisms of Genetic Risk for Impulsivity and Violence in Humans

Abstract: Neurobiological factors contributing to violence in humans remain poorly understood. One approach to this question is examining allelic variation in the X-linked monoamine oxidase A (MAOA) gene, previously associated with impulsive aggression in animals and humans. Here, we have studied the impact of a common functional polymorphism in MAOA on brain structure and function assessed with MRI in a large sample of healthy human volunteers. We show that the low expression variant, associated with increased risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 46 publications
(11 reference statements)
6
100
1
3
Order By: Relevance
“…Moreover, there was a gender-specific (only males) increase in the lateral orbitofrontal cortex (BA 47) volume bilaterally in the low expression variant of the MAO-A as compared with the high expression variant (Figure 3(B)). Meyer-Lindenberg et al (2006) reported the most robust structural changes in the cingulate cortex. The cingulate cortex is involved in the regulation of emotions and social behavior, a region with a very high serotonin transporter density (Mantere et al, 2002).…”
Section: History Of Neuroimaging In Psychopathsmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, there was a gender-specific (only males) increase in the lateral orbitofrontal cortex (BA 47) volume bilaterally in the low expression variant of the MAO-A as compared with the high expression variant (Figure 3(B)). Meyer-Lindenberg et al (2006) reported the most robust structural changes in the cingulate cortex. The cingulate cortex is involved in the regulation of emotions and social behavior, a region with a very high serotonin transporter density (Mantere et al, 2002).…”
Section: History Of Neuroimaging In Psychopathsmentioning
confidence: 96%
“…It has been suggested that the two dimensions of aggression are genetically dissociable (Meyer-Lindenberg et al, 2006). A recent neuroimaging study by Meyer-Lindenberg and colleagues (2006) reports a link between the X-linked monoaminoxidase A (MAO-A) gene and structural brain abnormalities.…”
Section: History Of Neuroimaging In Psychopathsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is believed that it leads to higher intolerance to adverse interactions, in the context of past victimization [21]. The nature-nurture relation that is established seems to take place through impairments in the neurodevelopment of the limbic system (which is rendered increased in size) and amygdala hyper-responsivity [22], which affect inhibitory capacities and general affective stability.…”
Section: Genetic Risk Factors To Antisocial Disordermentioning
confidence: 99%
“…Preclinical research shows a similar population trend, with a small proportion of rodents (between 15 and 30%) consistently exhibiting escalated attack behavior after alcohol intake Miczek et al 1992Miczek et al , 1998van Erp and Miczek 1997). It has been hypothesized that a preexisting genetic vulnerability predisposes an individual to drink and to engage in violence as a function of certain environmental influences (Higley and Bennett 1999;Higley et al 1996;Meyer-Lindenberg et al 2006).…”
mentioning
confidence: 93%